Typical Soil Redox Processes in Pentachlorophenol Polluted Soil Following Biochar Addition - Zhu, Min; Zhang, Lujun; Zheng, Liwei; Zhuo, Ying; Xu, Jianming; He, Yan (Frontiers in Microbiology, 2018)
Reductive dechlorination is the primary pathway for environmental removal of pentachlorophenol (PCP) in soil under anaerobic condition. This process has been verified to be coupled with other soil redox processes of typical biogenic elements such as carbon, iron and sulfur. Meanwhile, biochar has received increasing interest in its potential for remediation of contaminated soil, with the effect seldom investigated under anaerobic environment. In this study, a 120-day anaerobic incubation experiment was conducted to investigate the effects of biochar on soil redox processes and thereby the reductive dechlorination of PCP under anaerobic condition. Biochar addition (1%, w/w) enhanced the dissimilatory iron reduction and sulfate reduction while simultaneously decreased the PCP reduction significantly. Interestingly, however, PCP reduction was promoted by biochar when microbial sulfate reduction was suppressed by addition of typical inhibitor molybdate. The methanogenesis process was also significantly promoted with addition of both biochar and molybdate. Together with Illumina sequencing data regarding analysis of soil bacteria and archaea responses, our results suggest that under anaerobic condition, biochar may not helpful for remediation of PCP polluted soil since its application would suppress the reductive dechlorination of PCP through enhancing the electron transfer to more competitive electron acceptor (e.g. Fe(III)) instead of PCP and promoting the growth of sulfate reducer (Desulfobulbaceae and Desulfobacteraceae) to compete the limited electrons. Supplementary addition of molybdate while biochar application is suggested as an improved strategy for a better remediation results by coordinating the interaction between dechlorination and its coupled soil redox processes, with minimum production of toxic iron/sulfur reducing substances and emission of greenhouse gas (CH4) while maximum removal of PCP.